Diminished UV radiation enhances national cognitive ability, wealth, and institutions through health and education - León Eyzaguirre, Federico R. (2018)
Rindermann's cognitive capitalism disregards geographic causes of national wealth and postulates that IQ influences wealth through strengthened institutions, whereas a novel biogeographic theory posits that diminished UV radiation, by reducing cell oxidative stress and fatigue, increases industriousness and improves nations' wealth, thus generating favorable conditions for children's intellectual growth. This study tested predictions from both perspectives and also evaluated whether health + education mediates radiation's cognitive and economic effects. Analyses of data sets encompassing 96 countries yielded well-fitted structural equation models upholding the latter hypothesis and showing that radiation directly influences all variables, cognitive ability and income are unrelated, and the former and institutional strength behave as net dependent variables. The findings suggest that what national development requires is healthy and well-educated populations; enhanced cognitive ability, greater wealth, and strong institutions should follow. Geography appears to act on these variables through physiological processes and psychological constructs which deserve greater attention.